Health dialogue elements identified during health communication between nurses and patients with diabetes in the Maluti-a-Phofung municipality - Mosia, Dineo Kuki Joyce (University of the Free State, 2018)
Health communication is the primary aspect used in healthcare to promote the well-being of the public and to prevent diseases. Therefore, communication plays an important role in healthcare settings. Health information is disseminated to both individuals and the public through sharing knowledge on health and health management. Importantly, effective communication between healthcare providers and patients is needed to improve patients’ adherence to treatment, recovery, and their satisfaction with service delivery. The relationship between health dialogue and health communication was described. Elements related to health dialogue, which include antecedents and empirical referents, were discussed as indicated in the conceptual map. A checklist, consisting of the criteria which meet the expected behaviour, was developed and used to assess the extent to which health dialogue elements were used during health communication between nurses and diabetic patients in the Maluti-A-Phufong Municipality, Thabo Mofutsanyana District. The guideline for the use of the observational checklist was developed and used to guide the observers and improve the validity and reliability of data during the study. A quantitative, descriptive, cross-sectional design was used to describe the health dialogue elements employed during health communication between nurses and diabetic patients in the Maluti-A-Phufong Municipality, Thabo Mofutsanyana District. Individual nurses, who manage diabetic patients in thirty-one clinics of Maluti-A-Phofung Municipality, Thabo Mofutsanyana District, were conveniently selected to participate. One hundred and thirty-seven diabetic patients were involved in the study. The researcher also used a tape recorder to collect data. Nurses and patients were simultaneously observed. Thereafter, the researcher and the fieldworker gathered individual and private feedback from nurses and patients on questions addressing their experience on shared responsibility and decision making during consultation. The mentioned interviews lasted for five minutes or less. All nurses and patients involved in the study signed the consent forms. A biostatistician, who was consulted during planning of the study, made use of Statistical Analysis Software (SAS) to analyse the collected data. Frequencies and percentiles were used to summarize numerical and categorical variables. Differences between groups were assessed on a 95% confidence interval for unpaired data. Recommendations focused on the development and implementation of health education policies which will be used in all clinics and applied the same when managing patients with diabetes or any other chronic condition.
Keywords: Health communication; Health dialogue elements; Nurses and diabetic patients; Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2018